Does early vitamin B12 supplementation improve neurodevelopment and cognitive function in childhood and into school age: a study protocol for extended follow-ups from randomised controlled trials in India and Tanzania. Issue 2 (22nd February 2018) - Winje, Brita Askeland; Kvestad, Ingrid; Krishnamachari, Srinivasan; Manji, Karim; Taneja, Sunita; Bellinger, David C; Bhandari, Nita; Bisht, Shruti; Darling, Anne Marie; Duggan, Christopher P; Fawzi, Wafaie; Hysing, Mari; et al.
Abstract : Introduction: As many as 250 million children under the age of 5 may not be reaching their full developmental potential partly due to poor nutrition during pregnancy and the first 2 years of life. Micronutrients, including vitamin B12, are important for the development of brain structure and function; however, the timing, duration and severity of deficiencies may alter the impact on functional development outcomes. Consequently, to fully explore the effect of vitamin B12 on cognitive function, it is crucial to measure neurodevelopment at different ages, in different populations and with vitamin B12 supplementation at different times during the critical periods of neurodevelopment. Methods and analysis: In this project, we follow up children from four recently completed randomised placebo-controlled trials of oral vitamin B12 supplementation, two in India and two in Tanzania, to explore the long-term effects on neurodevelopmental outcomes and growth. All the included trials provided at least two recommended dietary allowances of oral vitamin B12 daily for at least 6 months. Vitamin B12 was supplemented either during pregnancy, early infancy or early childhood. Primary outcomes are neurodevelopmental status, cognitive function and growth later in childhood. We apply validated and culturally appropriate instruments to identify relevant developmental outcomes. All statistical analyses will be done according to intention-to-treat principles. The project provides an excellent opportunity to examine the effect of vitamin B12 supplementation in different periods during early life and measure the outcomes later in childhood. Ethics and dissemination: The study has received ethical approvals from all relevant authorities in Norway, USA, Tanzania and India and complies fully with ethical principles for medical research. Results will be presented at national and international research and policy meetings and published in peer-reviewed scientific journals, preferably open access. Trial registration number: NCT00641862 (Bangalore); NCT00717730, updated CTRI/2016/11/007494 (Delhi); NCT00197548 and NCT00421668 (Dar es Salaam).